Genetic variability of Phakopsora pachyrhizi accessed by microsatellite markers - Tschurtschenthaler, Nely Norder; Vieira, Elisa Serra Negra; Dalla Nora, Tatiane; Schuster, Ivan (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the genetic variability of Asian soybean rust in Brazil using microsatellite markers. Samples of Phakopsora pachyrhizi spores collected in the Southern, Southeastern, and Central West regions of Brazil were subjected to analysis of genetic variability, accessed with microsatellite markers specific for the fungus. Spores of the fungus were also collected in several soybean varieties in a same locality, including samples with reddish‑brown (RB) lesions. Among these samples, there was no variability. Tissues with RB lesions did not contain spores of the fungus and did not amplify with the specific markers for P. pachyrhizi. Genetic variability among samples collected in the three regions ranged from 0 to 0.36. A tendency to cluster samples of the Southern and Central West regions of Brazil in different groups was observed. The existence of genetic variability in P. pachyrhizi spore populations indicates that vertical genetic resistance, provided by single genes, is a risky strategy for soybean breeding programs that aim resistance to Asian soybean rust.